Immunoexpression of C4 Binding Protein in Oral Leukoplakia and Oral Squamous Cell Carcinoma - Mashhadiabbas, Fatemeh; Fayazi-Boroujeni, Masoume; Alizadeh, Akram; Namdari, Mahshid; Mirzaei, Seyed Abbas (Iranian journal of immunology, 2021)
The immune evasion of dysplastic cells plays an important role in suppressing the immune response and progression of malignancy. The role of the complement inhibitors in the development of oral epithelial dysplastic lesions and squamous cell carcinoma (SCC) is still unclear. This study aimed to assess the expression of C4 binding protein (C4BP) as a complement inhibitor in oral squamous cell carcinoma and leukoplakia. In this study, 94 samples were classified into four groups: leukoplakia with mild to moderate dysplasia, leukoplakia with severe dysplasia or carcinoma in situ, early invasive SCC, and invasive SCC. The expression of C4BP marker was evaluated by immunohistochemistry (IHC) and real-time PCR. The results were analyzed by the Kruskal-Wallis, Bonferroni adjusted Dunn's multiple comparison, and one-way ANOVA tests. The results of IHC revealed the expression patterns of C4BP in oral dysplasia and SCC, and indicated that the C4BP expression was not significantly different between different histopathological grades in epithelial cells and vessels (P=0.157 and P=0.123, respectively) but, it was significantly different in fibroblasts and lymphocytes (P=0.017 and P=0.043, respectively). The real-time PCR showed a significant correlation between the dysplasia grade and expression of C4BP (P<0.05). According to the results, C4BP is expressed in the cancerous tissue by the tumor cells and their surrounding stroma. In addition, upregulation of the C4BP gene as an inhibitor of the complement system is a possible strategy adopted by the tumor cells to evade the immune system.